More Hesselbein on leadership - Hesselbein, Frances (J-B Leader to Leader Institute/PF Drucker Foundation, 2012)
"Frances Hesselbein inspires people from all walks of life, from Fortune 500 CEOs to philanthropists, military general officers, young leaders, and nonprofit executives in every social sector. Leadership, she teaches, begins not with what you do, but with who you are."--Jim Collins, author of iGood to Great/i and iHow the Mighty Fall/i/ Get wisdom and advice on a range of timeless leadership topics and challenges from Frances Hesselbein, president and CEO of the acclaimed Frances Hesselbein Leadership Institute. This collection of compelling articles is amust-read for leaders who need to be prepared to guide their organizations into an uncertain future. With rare intelligence and keen insight, she:/ ulliOffersan impassioned discussion about her zeal for diversity and inclusion/liliTakes a hard look at today's pervasiveatmosphere of cynicism and mistrust/liliReveals how leaders can change the lives of children, schools, and communitities/liliExtols a new generation that relate tothe maxim "Leadership is a matter of how to be, not how to do"/liliShows what it takes to be a true leader during a crisis/liliAnd more. /li/ul